Antioxidant Potential of the Asteraceae Family in Counteracting Free Radicals in Cigarette Smoke: An Overview - Aulia Syafadilla Azali; Muhammad Andy Rajab; Sofiani Lathifah; Akrom (Jurnal FARMASIMED (JFM), 2025)
Cigarette smoke exposure triggers oxidative stress in the respiratory system through an increase in free radicals and a decrease in endogenous antioxidant activity, which contributes to lung damage and chronic diseases such as COPD and lung cancer. This study aims to investigate the potential of species from the Asteraceae family as a source of natural antioxidants in protecting the lungs and trachea from damage caused by exposure to free radicals in cigarette smoke. The method used is a Systematic Literature Review (SLR) with reference to the PRISMA 2020 guidelines. Literature searches were conducted systematically through the PubMed, ScienceDirect, and Google Scholar databases until June 2025. The inclusion criteria included in vivo studies using Asteraceae plant extracts in animals with induced oxidative stress in the respiratory system, as well as involving the measurement of biomarkers such as MDA, GSH, SOD, and CAT. Of the 198 articles found, 10 articles met the criteria and included species such as Tridax procumbens, Chromolaena odorata, Pulicaria petiolaris, and Baccharis retusa. The results showed that these species had significant antioxidant activity through their flavonoid, polyphenol, and triterpenoid compound content. However, most studies did not use a direct cigarette smoke exposure model. In conclusion, the Asteraceae family has great potential as a source of natural antioxidants to protect the respiratory system from oxidative stress, although further research with more relevant exposure models is needed. Toxicology and metabolomics approaches are also needed to strengthen the evidence for practical application in the treatment of lung diseases caused by cigarette smoke.